Hemolysis-in-gel test for demonstration of Chlamydia antibodies. - Lycke, E (1976)
Sheep erythrocytes were coated with antigens of a strain of Chlamydia trachomatis serotype D. Chlamydial antibodies in sera from patients with salpingitis or pneumonia were demonstrated by passive hemolysis in agarose gel.